CORPORATE GOVERNANCE SYSTEMS’ IMPACT ON THE GLOBAL AUTOMOTIVE INDUSTRY’S COMMUNICATION OF FINANCIAL RATIOS - Tower, Greg; Aripin, Norhani; Ahmad, Raja Adzrin Raja; Tower, Spence (The journal of contemporary issues in business and government, 2010)
The influence of corporate governance systems on the reporting practices of the global automotive industry firms is investigated. This industry is important due to its truly global scope and the economic ripple effect of its vastly intertwined supply chain. The extent of financial ratio disclosure information in the annual reports of the world’s top automotive firms is measured. The findings show that although most firms are profitable in 2008, they are sparse in communicating their financial ratio positions. Most of these massive automotive firms are deemed to have good corporate governance systems. However, improvements could be made with regard to corporate governance practices. These corporate governance systems are found to be a statistically positive influence on the extent of financial ratio disclosures. Improved communication should enhance stakeholder understanding of the actual financial position of firms in this most highly visible global industry.